Linguistic familiarity and complexity of language competence recovery in Sundanese-Indonesian bilingual aphasia patients - Nasrullah, Riki; Suganda, Dadang; Firdaus, Winci; Isam, Hishamudin (Indonesian Journal of Applied Linguistics, 2024)
The incidence of stroke in Indonesia continues to increase, which causes an increase in cases of aphasia. Meanwhile, the Regulation of the Minister of Health of the Republic of Indonesia Number 81 of 2014 does not explicitly regulate the mechanism of speech therapy for bilingual aphasia patients, including those of Sundanese-Indonesian bilingual aphasia. The study aimed to find verbal expressions of bilingual aphasia patients, patterns of language competence recovery, and determinants of the language competence recovery process in Sundanese-Indonesian bilingual aphasia patients. We analyzed the data 4 Sundanese-Indonesian bilingual aphasia patients at Al Islam Hospital, Bandung, and National Brain Center Hospital, Jakarta, using a list of guiding questions and evaluation of TADIR: Tes Afasia untuk Diagnosa, Informasi, dan Rehabilitasi (Aphasia Test for Diagnosis, Information, and Rehabilitation). While the limited sample size of four patients may affect the generalizability and reliability of the findings, the study provides a crucial insight into recovery patterns specific to Sundanese-Indonesian bilingual aphasia patients. This study showed selective, asymmetric, and symmetric recovery patterns in bilingual Sundanese-Indonesian patients. This study reinforces the assumption that linguistic familiarity is the main factor in the recovery of language competence in Sundanese-Indonesian bilingual aphasia patients.